The Parable of the Mustard Seed in the Gospel of Mark 4:30-34 - Patrisia Putri; Puput, Puput; Ribka Wahyu Christiani; Sarmauli (Tinta Emas Institute, 2024)
This study explores the concept of the Kingdom of Allah through the parable of the mustard seed in Mark 4:30-34, illustrating its growth from small beginnings to greatness. Using a qualitative method, the research examines how Mark's Gospel emphasizes faith, hope, and transformation. The Kingdom of Allah, as described in Romans 14:17, is about righteousness, peace, and joy through the Holy Spirit, bestowed upon those who surrender to divine guidance. Mark, though not named in the Gospel, is traditionally recognized as its author. He grew up in Jerusalem and was part of the first generation of Christians, collaborating with Paul, Barnabas, and Peter. The parable of the mustard seed highlights the potential for significant growth from something seemingly insignificant. This metaphor teaches that small faith can become powerful with proper nurturing. The study suggests that this parable encourages developing faith, fostering inclusivity, and striving for sustainable personal and community growth. The message remains relevant today, inspiring individuals to cultivate their faith and contribute positively to their communities.